PENGEMBANGAN SOAL-SOAL BERPIKIR KOMPUTASIONAL BERBASIS ETNOMATEMATIKA KEPULAUAN PADA TARIAN ADAT MALUKU BARAT DAYA - Inuhan, Michael; Rupilele, Karolina; Kurniati MA, Ratnah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop an ethnomathematics-based computational thinking assessment instrument using the traditional dance of the Klis community in Southwest Maluku for junior high school students. The study employed a Research and Development (R&D) approach consisting of needs analysis, instrument design, expert validation, limited trials, and product revision. The instrument was tested on 30 junior high school students, and the data were analyzed using Anates V4 to evaluate validity, reliability, discrimination index, and difficulty level. The results indicated that all items were valid, with very high reliability (coefficient = 0.97), good discrimination indices (46.88%–60.23%), and moderate difficulty levels, demonstrating that the instrument is appropriate for mathematics assessment. The integration of ethnomathematics through the Klis traditional dance enabled the development of tasks that assess key computational thinking skills, including decomposition, abstraction, pattern recognition, and algorithm design. These findings suggest that incorporating local cultural contexts into assessment enhances both the quality of mathematics evaluation and students' appreciation of their cultural heritage. Therefore, the developed instrument is valid, reliable, and suitable for junior high school mathematics learning, providing an innovative assessment alternative that simultaneously promotes computational thinking and supports the preservation of local culture.